2014
DOI: 10.1128/jvi.01712-14
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Human Immunodeficiency Virus Type 1 (HIV-1)-Infected Cells License Quiescent CD4 + T Lymphocytes To Replicate HIV-1 through a Nef- and ADAM17-Dependent Mechanism

Abstract: Resting CD4؉ T lymphocytes resist human immunodeficiency virus (HIV) infection. Here, we provide evidence that exosomes from HIV-1-infected cells render resting human primary CD4 ؉ T lymphocytes permissive to HIV-1 replication. These results were obtained with transwell cocultures of HIV-1-infected cells with quiescent CD4؉ T lymphocytes in the presence of inhibitors of exosome release and were confirmed using exosomes purified from supernatants of HIV-1-infected primary CD4؉ T lymphocytes. We found that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 35 publications
4
149
1
1
Order By: Relevance
“…To date, though, there is no convincing indication that retroviruses use this method. Various HIV-1 RNAs and proteins have been detected in EVs, and effects have been imputed to some of these (8,(46)(47)(48)(49). In one report, several unspliced HIV RNA sequences were found in association with exosomes, consistent with full-length genome incorporation (46).…”
Section: Do Other Enveloped Viruses Shuttle Genomes In Evs?mentioning
confidence: 71%
“…To date, though, there is no convincing indication that retroviruses use this method. Various HIV-1 RNAs and proteins have been detected in EVs, and effects have been imputed to some of these (8,(46)(47)(48)(49). In one report, several unspliced HIV RNA sequences were found in association with exosomes, consistent with full-length genome incorporation (46).…”
Section: Do Other Enveloped Viruses Shuttle Genomes In Evs?mentioning
confidence: 71%
“…Delivery of the EV-associated Nef to T cells affects these cells in several ways. First, the transferred Nef may activate T cells, rendering them more susceptible to HIV infection (54). Second, EVs can deliver Nef to some of the bystander CD4 + T cells and induce cell senescence or death (55).…”
Section: To Be or Not To Be Infected: Evs In Pro-and Antiviral Stratementioning
confidence: 99%
“…Previous studies in 293T cells and quiescent CD4 T cells suggested a role for Nef in TNF production through its effects on exosomes (97,98). Therefore, we assessed the contribution of Nef to TNF release by infecting MT4C5 cells with viruses deleted for vpr or for nef or deleted for both genes (see Fig.…”
Section: Vpr Enhances Tnf Secretion By Infected Cellsmentioning
confidence: 99%